Energy densities: a systematic approach to correlation in density functional theory - Irons, Tom J.P. (2019)
Density functional theory (DFT) has grown to become by far the most widely applied method in the modelling of electronic systems yet, in contrast to wavefunction-based ab initio methods, the reliability of a DFT calculation can be uncertain. This is because the essential ingredient required for a DFT calculation to be meaningful - the exchange & correlation energy functionals, are approximations for a type of electronic interaction with an unknown functional form. Whilst there exist types of system for which DFT does not provide a useful model - those with significant dispersion interactions and those with near-degenerate states, seeking improvements to DFT in these areas can be far from straightforward since the exchange & correlation functionals cannot be systematically improved.